Question

Simplify the following expression: -6i(3-2i)

Quadratics
ANSWERED
asked 2021-08-18
Simplify the following expression:
-6i(3-2i)

Expert Answers (1)

2021-08-19
We're given:
\(\displaystyle-{6}{i}{\left({3}-{2}{i}\right)}\)
Multiply:
\(\displaystyle-{6}{i}{\left({3}-{2}{i}\right)}={\left({6}{i}\times{3}\right)}-{\left({6}{i}\times{2}{i}\right)}={18}{i}-{12}{i}^{{2}}\)
Substitute \(\displaystyle{i}^{{2}}=-{1}:\)
\(\displaystyle{18}{i}-{12}{i}^{{2}}={18}{i}-{\left({12}{\left(-{1}\right)}\right)}\)
\(\displaystyle={18}{i}-{\left(-{12}\right)}={18}{i}+{12}\)
The answer:
\(\displaystyle-{6}{i}{\left({3}-{2}{i}\right)}={18}{i}+{12}\)
10
 
Best answer

expert advice

Have a similar question?
We can deal with it in 3 hours
...